Synthesis and optical properties of P5+ co-doped Ba3SiO5:Eu2+ orange persistent phosphor. (January 2018) - Choi, Seung Hee; Kwon, Seok Bin; Humayoun, Usama Bin; Park, Won Kyu; Toda, Kenji; Kakihana, Masato; Masaki, Takaki; Yang, Woo Seok; Song, Young Hyun; Yoon, Dae Ho
Abstract: By co-doping the P 5+ ions into Ba3 SiO5 :Eu 2+, we synthesized new orange persistent phosphor using cellulose assisted liquid phase precursor (LPP) method. The emission spectra showed a typically broad orange emission band centered at 575 nm attributed to the 4f 6 5d 1 → 4f 7 transition of Eu 2+ ions under 400 nm excitation source. The persistent luminescence property of Eu 2+ doped Ba3 SiO5 orange phosphor was enhanced by co-doping non-equivalent phosphorus ions into silicon sites. This enhancement can be explained by formation of the trapping center due to the charge compenstation. Consequently, the afterglow decay exhibited an orange emission for more than 5 min after irradiation at under 365 nm for 1 min. Highlights: Ba3 SiO5 :Eu 2+, P 5+ new orange persistent phosphor synthesized using cellulose assisted liquid phase precursor method. P 5+ doping can improve the persistent luminescence property. Trap center storing excitation energy is proposed by charge compensation.